Neuroprotective role of gallic acid in aflatoxin Bi-induced behavioral abnormalities in rats (2020)
The neurotoxic impact of dietary exposure to aflatoxin Bi (AFBJ is documented in experimental and epidemiological studies. Gallic acid (GA) is a triphenolic phyto- chemical with potent anticancer, anti-inflammatory, and antioxidant activities. There is a knowledge gap on thè influence of GA on AFBi-induced neurotoxicity. This study probed thè influence of GA on neurobehavioral and biochemical abnormalities in rats orally treated with AFBi per se (75pg/kg body weight) or administered together with GA (20 and 40mg/kg) for 28 uninterrupted days. Behavioral endpoints obtained with video-tracking software demonstrated sig-nificant (p<.05) abatement of AFBrinduced anxiogenic-like behaviors (increased freezing, urination, and fecal bolus discharge), motor and locomotor inadequacies, namely increased negative geotaxis and diminished grip strength, absolute turn angle, total time mobile, body rotation, maximum speed, and total distance traveled by GA. The improvement of exploratory behavior in animals that received both AFBi and GA was confirmed by track plots and heat maps appraisal. Abatement of AFBj-induced decreases in acetylcholinesterase activity, antioxidant status and glutathione level by GA was accompanied by a marked reduction in oxidative stress markers in thè cerebellum and cerebrum of rats. Additionally, GA treatment abro- gated AFBi-mediated decrease in interleukin-10 and elevation of inflammatory in- dices, namely tumor necrosis factor-a, myeloperoxidase activity, interleukin-l|3, and nitric oxide. Further, GA treatment curtailed caspase-3 activation and histological injuries in thè cerebral and cerebellar tissues. In conclusion, abatement of AFBi-induced neurobehavioral abnormalities by GA involves anti-inflammatory, antioxidant, and antiapoptotic mechanisms in rats.